Digital stethoscope - Tan, Meng Yik (2015)
This project aims to understand more about how the heart functions and how acoustic stethoscope is used to listen to the heart sounds. There are four heart sounds S1, S2, S3 and S4 and there are generated when the valves in the heart open and close to allow unidirectional blood flow. Murmurs are also sometimes present and are usually abnormal. Murmurs are normally very faint, therefore hard to hear. Acoustic stethoscope is the earliest form of hearing device used for listening to heart sounds. It was invented by a French named named Rene Theophile Hyacinthe Laënnec. Over the years stethoscope has been modified and improved However, there are some complications with the currently popular acoustic stethoscope. Some disadvantages are the performances are directly linked to the audio capability of the user. Also when the level of environmental noise is high it makes it difficult to listen to the heart sound of the patient, it invalidate auscultations. This leads to the idea of using electronic stethoscope to eliminate these disadvantages. Electronic stethoscope is a stethoscope that first picked up the sound of the heart using the same conventional bell. Then the acoustic sound of the heart is converted to electrical signals. These electrical signals are usually small; therefore the signal has to be amplified. Then adding in a low pass signal helps to filter can clean up noises of higher frequencies that are unwanted. The electrical signal are then send into a power amplifier to boost the power of the speaker and drive a stereo speaker so that the heart sounds can be heard. If analysis of the wave of the heart sound is required, an ADC is needed to convert the signal to digital signal and fed into the computer.